Controlling jako wsparcie nadzoru korporacyjnego w grupie kapitałowej - Karmańska, Anna; Szumielewicz, Wojciech (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The main question of this article is controlling carried out on the capital group's level. The above considerations are focused on the specification of certain problems referring to (1) corporate governance in holdings and to (2) controlling as a tool in such governance. In this context certain relationships between corporate governance and controlling have been shown and on this basis -different dimensions and elements of controlling oriented at management problems which are appearing on the level of the capital group as a whole. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 95-110